Pengaruh Beban Kerja dan Kompensasi terhadap Kinerja Dosen melalui Kepuasan Kerja sebagai Variabel Intervening di Universitas Muhammadiyah Enrekang - Nurlativa Beta; Mashur Razak; Didi Haryono (Movere Journal, 2026)
Abstract: This research  aims to analyze the influence of Workload and Compensation on Lecturer Performance through Job Satisfaction at the University of Muhammadiyah Enrekang." The analytical tool used in this research is SEM-PLS, while the population in the research is 82 lecturers at Muhammadiyah University Enrekang. The sample used in this research was 82 people. This research aims  to analyze the influence of compensation on lecturer performance, to analyze the influence of workload on performance  to analyze job satisfaction on lecturer performance, to analyze the influence of workload on job satisfaction, To analyze the influence of Compensation on Job atisfaction, To analyze the influence of Workload on lecturer performance through Job Satisfaction at Muhammadiyah University Enrekang,  To analyze the influence of workload on lecturer performance through Job Satisfaction at Muhammadiyah University Enrekang .